2012
DOI: 10.1111/j.1447-0756.2011.01734.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 17β‐estradiol on the release of monocyte chemotactic protein‐1 and MAPK activity in monocytes stimulated with peritoneal fluid from endometriosis patients

Abstract: The ability of E2 to modulate MCP-1 production is impaired in ePF-treated monocytes, which may be related to regulation of MAPK activity. These findings suggest that the failure of E2 to suppress ePF-treated production of MCP-1 may be involved in the pathogenesis of endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The implication of Akt, ERK1/2, and p38 in this C1P action is consistent with previous work by other groups showing that MCP-1 upregulated these kinases in different cell types, including rat aortic smooth muscle cells (55), proximal tubular cells (51), 3T3-L1 preadipocytes (56), vascular smooth muscle cells (12), and monocytes (33). Nonetheless, although MCP-1 release has been associated with activation of p38 in many instances (8,33,56; and our unpublished observations), other studies have indicated that this kinase is not involved in this process (31,35), and therefore the role of p38 in stimulation of MCP-1 secretion remains controversial.…”
Section: Discussionsupporting
confidence: 79%
“…The implication of Akt, ERK1/2, and p38 in this C1P action is consistent with previous work by other groups showing that MCP-1 upregulated these kinases in different cell types, including rat aortic smooth muscle cells (55), proximal tubular cells (51), 3T3-L1 preadipocytes (56), vascular smooth muscle cells (12), and monocytes (33). Nonetheless, although MCP-1 release has been associated with activation of p38 in many instances (8,33,56; and our unpublished observations), other studies have indicated that this kinase is not involved in this process (31,35), and therefore the role of p38 in stimulation of MCP-1 secretion remains controversial.…”
Section: Discussionsupporting
confidence: 79%
“…While TGF‐β1 is well‐documented to induce EMT, the intracellular signaling responsible for this induction includes activation of ERK1/2, p38 MAPK, and JNK . Again, ERK1/2, p38 MAPK, and JNK have all been reported to be involved in endometriosis …”
Section: Mutations Of Cancer Driver Genes In Endometriosis and Their mentioning
confidence: 99%
“…261 Again, ERK1/2, p38 MAPK, and JNK have all been reported to be involved in endometriosis. [262][263][264][265][266][267] | 377…”
Section: Krasmentioning
confidence: 99%
“…After treating monocytes with control peritoneal fluid (cPF) or endometriotic peritoneal fluid (ePF), the addition of E2 to the culture suppresses MCP1 release from cPF-treated monocytes. However, E2 does not suppress MCP1 release from ePF-treated monocytes (Lee et al 2012). E2 promotes a pro-inflammatory environment by increasing secretion of IL6 and TNF from peritoneal macrophages from women with endometriosis compared to control women.…”
Section: Pathogenesis and Progression Of Endometriosismentioning
confidence: 99%